Targeting Pericytes for Angiogenic Therapies. (May 2014) - Kelly‐Goss, Molly R.; Sweat, Rick S.; Stapor, Peter C.; Peirce, Shayn M.; Murfee, Walter L.
Abstract In pathological scenarios, such as tumor growth and diabetic retinopathy, blocking angiogenesis would be beneficial. In others, such as myocardial infarction and hypertension, promoting angiogenesis might be desirable. Due to their putative influence on endothelial cells, vascular pericytes have become a topic of growing interest and are increasingly being evaluated as a potential target for angioregulatory therapies. The strategy of manipulating pericyte recruitment to capillaries could result in anti‐ or proangiogenic effects. Our current understanding of pericytes, however, is limited by knowledge gaps regarding pericyte identity and lineage. To use a music analogy, this review is a "mash‐up" that attempts to integrate what we know about pericyte functionality and expression with what is beginning to be elucidated regarding their regenerative potential. We explore the lingering questions regarding pericyte phenotypic identity and lineage. The expression of different pericyte markers (e.g., SMA, Desmin, NG2, and PDGFR‐β) varies for different subpopulations and tissues. Previous use of these markers to identify pericytes has suggested potential phenotypic overlaps and plasticity toward other cell phenotypes. Our review chronicles the state of the literature, identifies critical unanswered questions, and motivates future research aimed at understanding this intriguing cell type and harnessing its therapeutic potential.